The Hidden Cost of Innovation: Unpacking the Price Tag of IBM Watson Health for Hospitals - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The promise of Artificial Intelligence AI in healthcare has long been heralded as a transformative force, capable of revolutionizing diagnostics, treatment p...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care